Iz zgodovine vesolja v prihodnost človeštva - Makarovič, Jan (Teorija in praksa, 2011)
The process of globalisation of the contemporary world is on the one hand reflected in a growing interconnectedness of humanity across geographical borders, and on the other hand in an ever more fatal interdependence between man and nature, while the following is of special importance: (a) man comes from nature; (b) he creatively transforms it; and (c) this transformation affects also the relations between men themselves - consequently man, through the transformation of nature, indirectly forms himself. This is only a specific case of a gradual complexification, such as it can be observed at the cosmic level from the big bang on, and is at the same time dependent on the energy density flow into matter, which can be expressed in physical entities, as shown in 2001 by the American astrophysicist Eric Chaisson. This model can be applied also to the development of human society. Nature shaped by man, which is in Marx terminology synonymous to the development of the 'productive forces', can be primarily understood as the exploitation of energy resources necessary to maintain a certain level of social complexity. The contemporary ecological crisis can be seen as a problem of limited energy resources resulting from a growing social complexity. The solution can be sought in a growing social cooperation, in the eradication of social inequalities and of the fetishism of private property, as well as in the globalisation of science, which was professed by Marx. The big history, the approach by a Dutch historian Fred Spier, is put forward as an example of this kind of globalisation.
Keywords: Globalizacija; Globalization; Modern society; Sodobna družba; Narava; Nature; Ecological crisis; Ekološka kriza; družba; society; science; znanost; energija